An Investigation of Critical Success Factors for the Implementation of Enterprises Resource Planning System in Chinese Small and Medium Enterprises - Dongxia, Wang (2017)
Enterprise resource planning system (ERP) has become one of the most important application information technologies for enterprise. However, the implementation of ERP system in Chinese small and medium enterprises (SMEs) is not very successful. The basic purpose of this paper is to find and verify the critical success factors (CSFs) of ERP implementation in Chinese enterprises under the specific context in China.